Efeitos de populações de plantas e da adubação mineral sobre misturas de cultivares de feijão (Phaseolus vulgaris L) - Gastim Pessanha , Gilberto; Vieira , Clibas; Américo Cardoso, Antônio (Revista Ceres, 2025)
Experimental studies have shown that mixtures of bean (Phaseolus vulgaris L.) cultivars have transitory duration, because the weak competitors are quickly eliminated due to inter-genotypic competition. However, in the Zona da Mata area, state of Minas Gerais, mixtures of bean cultivars are quite common, showing that some factors are contributing to preserve them.